2021
DOI: 10.19093/res11094
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the causality between economic growth, financial development and inflation in sixteen high-income countries

Abstract: This paper examined the relationship between economic growth, inflation, stock market development, and banking sector development for a panel of sixteen high-income countries for the period from 2001 to 2016, by using the mechanism impulse response functions and Granger causality tests derived from a panel vector autoregressive model. The evidence of bidirectional causality between all variables in the model was found. Overall, feedback and supply-leading theories have been confirmed in the literature. A plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…The supply-leading hypothesis (Schumpeter, 1912;Christopoulos & Tsionas, 2004;Küçüksakarya, 2021) is supported, meaning that the capital allocation provided by private banks, the more liquid stock markets, the banking efficiency, and the stability of the financial system can lead to economic growth. Moreover, the two-way causality between bank assets, liquid liabilities, non-performing loans, and economic growth is consistent with the findings of Demetriades and Hussein (1996), Al-Yousif (2002), Apergis et al (2007), Pradhan et al (2018) and Fuinhas et al (2020). In other words, the expansion and stability of the banking system can lead to economic growth, and the level of economic activity can lead to an increase in the size and stability of the banking sector.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The supply-leading hypothesis (Schumpeter, 1912;Christopoulos & Tsionas, 2004;Küçüksakarya, 2021) is supported, meaning that the capital allocation provided by private banks, the more liquid stock markets, the banking efficiency, and the stability of the financial system can lead to economic growth. Moreover, the two-way causality between bank assets, liquid liabilities, non-performing loans, and economic growth is consistent with the findings of Demetriades and Hussein (1996), Al-Yousif (2002), Apergis et al (2007), Pradhan et al (2018) and Fuinhas et al (2020). In other words, the expansion and stability of the banking system can lead to economic growth, and the level of economic activity can lead to an increase in the size and stability of the banking sector.…”
Section: Discussionsupporting
confidence: 85%
“…More recently, two additional hypotheses have been identified in the literature. The hypothesis of feedback causality, meaning the existence of two-way causality between financial development and economic growth (Demetriades & Hussein, 1996;Apergis et al, 2007;Al-Yousif, 2002;Calderón & Liu, 2003;Kar et al, 2011;Swamy & Dharani, 2018, Fuinhas et al, 2020Nguyen et al, 2021). Finally, the neutrality hypothesis supposes the absence of causality between financial and economic growth and the role of finance in economic growth is overemphasized (Lucas, 1988;Shan et al, 2001;Hsueh et al, 2013;Stolbov, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…So the wireless network is data centric [12]. (5) Resources are limited to most currently deployed in environmental monitoring, whose nodes are stationary, especially in areas where poor environment or humans cannot reach, and it is unrealistic to recharge the nodes [13].…”
Section: Empirical Research Methods Of the Relationship Between Financial Development And Economic Growth Based On Intelligent Algorithmsmentioning
confidence: 99%
“…Furthermore, the results confirmed that the current development of the financial sector is significantly positively influenced by the policies implemented in the previous period. Fuinhas et al (2021) used Granger causality assessments based on a panel vector autoregressive framework, as well as mechanism impulse response functions, to examine the relationships between economic growth, inflation, stock market development, and banking sector development in sixteen high-income countries from 2001 to 2016. Their findings indicate a two-way relationship between financial progress and inflation.…”
Section: Financial Development and Inflation Ratementioning
confidence: 99%